Repurposing Fragile X Drugs to Inhibit SARS-CoV-2 Viral Reproduction - Westmark, Cara J.; Kiso, Maki; Halfmann, Peter; Westmark, Pamela R.; Kawaoka, Yoshihiro (Frontiers in Cell and Developmental Biology, 2020)
The COVID-19 pandemic is a global health crisis that requires the application of interdisciplinary research to address numerous knowledge gaps including molecular strategies to prevent viral reproduction in affected individuals. In response to the Frontiers Research Topic, “Coronavirus disease (COVID-19): Pathophysiology, Epidemiology, Clinical Management and Public Health Response”, this Hypothesis article proposes a novel therapeutic strategy to repurpose metabotropic glutamate 5 receptor (mGluR5) inhibitors to interfere with viral hijacking of the host protein synthesis machinery. We review pertinent background on SARS-CoV-2, fragile X syndrome (FXS) and metabotropic glutamate receptor 5 (mGluR5) and provide a mechanistic-based hypothesis and preliminary data to support testing mGluR5 inhibitors in COVID-19 research.